Tikmũũn yĩy ax tinã xohi xi xahĩnãg - Sons e pedaços da língua Maxakalí: Descrição da fonologia e morfologia de uma língua Macro-Jê - Mário André Coelho da Silva (2020)
This doctorate thesis aims at providing a description of phonological and morphological aspects of the Maxakalí language. It belongs to the Macro-Jê stock, spoken in the region of Vale do Rio Mucuri (Mucuri River Valley), in the state of Minas Gerais, Brazil. The language has nine consonant phonemes, /p, t, c, k, b, d, ɟ, ɡ, h/, and ten vowel phonemes /i, ĩ, ɨ, ɨ̃, u, ũ, ɛ, ɛ̃, a, ã/. Due to increased contact with Brazilian Portuguese, its consonant inventory is undergoing a process of rearrangement, meaning that nasal consonants [m, n̪, ɲ] and lateral [l̪] are becoming phonologically distinctive. Its maximum syllabic structure is /CCVC/ and its minimum word is composed by two syllables, which in turn form the iambic foot. Among its main phonological phenomena, it is possible to highlight: the palatalization of velar consonants in coda, after a syllabic nucleus filled by an front vowel; the lenition of coda consonants, which vary in their realization, from allophones with total occlusion of the oral cavity, to vowel allophones; the vowel lowering caused by the consonant in coda and the transition glides, the result of coarticulating some vowels and consonants’ vowel allophones. There are some phenomena in the language regarding its nasality as well. Maxakalí relies on three types of spreading of the nasal feature. Two of them come from a stressed nasal vowel: there is one instance of spreading into the syllabic coda and another one towards the left margin of the morpheme, which is only blocked by voiceless segments. A third type takes place in the same left margin and is responsible for pre-nasalization of voiced oral segments in the beginning of words and for the near absence of stems that begin with a phonetic oral vowel. The suffix for diminutives causes a similar spreading to the one originated in the stressed vowel; however, it is only halted by an onset at the stem. In nominal morphology, there is a semantic distinction of crucial importance in the language, that is: the division between inalienable and alienable. The first of those classes has an internal argument, which indicates the owner of the stem’s referent, which must be obligatory expressed by a person index or by a noun phrase, while the second class does not carry that mandatory marking. That makes monosyllabic alienable noun stems stretch in given contexts, in order to achieve the well-formedness of the phonological foot. Verbs, on the other hand, rely on an ergative alignment in the realis mood and on an ergative split in the irrealis mood. That split can be found, as with nouns, in intransitive verbs, and it causes an elongation of the stem in active intransitive verbs, as they do not select an internal argument and, consequently, stretch for the well-formation of the foot. It is possible to note, therefore, that Maxakalí has a strong interaction between the phonological, morphological, syntactic and semantic components, and that a description of its linguistic system must consider all these factors.